Physico-geographical caracterization of the system that influences the multi-hazards in the sub-basin of Caldera River, Panama - Espinosa-Vega, Catalina Elvira (Universidad Autónoma de Tamaulipas, 2017)
The characterization of the physico-geographical system is a tool used to determine the multi-hazards generated by natural phenomena. The term multi-hazard describes the presence of more than one relevant hazard in the geosystem with different levels of interaction. The aim of this work was the characterization of the physico-geographical factors that can be considered as multi-hazard, and influence the disaster risk for the sub-basin of Caldera River, Panama. A systemic analysis of the geology, geomorphology, climatology, soil science and hydrography of the zone was conducted. Such analysis was complemented by fieldwork, using the direct method on the base of the expert criterion or heuristic method. The results indicate that the main hazards occurring in the study area are related to seismic and volcanic issues and its high vulnerability due to slope instability and flooding. These hazards and their relationship with anthropic action need to be considered in land use plans and disaster risk management in this area of Panama.